التحليل الاقتصادي لأثر متغيرات التنمية الزراعية في العراق باعتماد نموذج "VAR" للمدة "1990-2021" - محمد، مصطفى جاسم; شريف، محمد عمر (جامعة تكريت - كلية الإدارة والاقتصاد, 2023)
تعد متغيرات الاقتصاد الكلي من الوسائل التي يتم من خلالها قياس كفاءة أداء القطاعات الاقتصادية، بما في ذلك القطاع الزراعي، لأنها تهتم بدراسة كيفية الوصول إلى مستوى للقطاع، من خلال معرفة التغيرات التي تحدث فيه ومعدلات نموها، اعتمد البحث على بيانات للظاهرة المستهدفة بالدراسة من خلال سلسلة زمنية شملت المدة (1990-2021)، إذ أجري التحليل الإحصائي للأنموذج الاقتصادي المعتمد بالدراسة نموذج الانحدار الذاتي (VAR) والذي تضمن الناتج المحلي الزراعي كعامل تابع بينما شملت العوامل المستقلة رأس المال التراكمي الثابت، والقوى العاملة بالقطاع الزراعي، والقروض الزراعية، وكذلك قيمة الاستثمارات الزراعية كعوامل مستقلة، إذ تم تحديد متغيرات النموذج واختبار فرضية سكون السلاسل الزمنية من خلال التكامل المشترك باعتماد اختبار (Dicky Fuller Augmented) أوضح التحليل الاقتصادي للنموذج المقدر وجود أثر معنوي موجب لكل من رأس المال التراكمي الثابت والعمالة الزراعية وقيمة القروض الزراعية، إذ بلغت المرونات الجزئية لهذه المتغيرات (0.577) و(0.0184) و(0.0602) على التوالي، بينما أعطى التحليل أثرا معنويا سالبا لمتغير قيمة الاستثمارات الزراعية الذي بلغت مرونته (0.0529). أوصت الدراسة وبناء على النتائج التي تم التوصل إليها بضرورة الاستغلال الكفء للبنى التحتية التي تشكل جزء من قطاع الإنتاج الزراعي كذلك زيادة مستوى التقنية في الإنتاج الزراعي كاستخدام المكننة الزراعية وطرق الري الحديثة لتوسعة الاستثمارات الزراعية وإتباع أساليب ناجحة لإدارة التخصيص السليم للإنفاق الاستثماري الزراعي تجنبا وبالتالي تلافي الأثر السلبي للاستثمار الزراعي على الناتج المحلي الزراعي ومن ثم على نمو الناتج المحلي الإجمالي ونمو الاقتصاد. Macroeconomic variables are one of the means by which the efficiency of the performance of economic sectors, including the agricultural sector, it measured, because it is concerned with studying how to reach the level of equilibrium for the sector, by knowing the changes that occur in it and its growth rates. The research relied on data for the phenomenon targeted by the study from during a time series that included the period (1990-2021). The statistical analysis it conducted for the economic model approved by the study using the (VAR) technique, which included the agricultural domestic product as a dependent factor, while the independent factors included the fixed cumulative capital and the labor force in the agricultural sector. In addition, agricultural loans, as well as the value of agricultural investments as dependent factors, as the model variables were determined and the time series static hypothesis it tested through counteraction by adopting the (Dicky Fuller Augmented) test. The economic analysis of the estimated model showed that there was a significant positive effect for each of the cumulative fixed capital, agricultural labor and the value of agricultural loans, as the partial elasticities of these variables amounted to (0.577), (0.0184) and (0.0602), respectively. While the analysis gave a significant negative effect of the variable value of agricultural investments, which had a flexibility of (-0.0529). Based on the results reached, the study recommended the need for efficient utilization of the infrastructure that forms part of the agricultural production sector, as well as increasing the level of technology in agricultural production, such as the use of agricultural mechanization and modern irrigation methods to expand agricultural investments. And adopting successful methods to manage the proper allocation of agricultural investment spending in order to avoid waste and thus avoid the negative impact of agricultural investment on the agricultural domestic product and then on the growth of the gross domestic product and the growth of the economy.
Keywords: التنمية الاقتصادية -- الاستثمارات الزراعية -- الانحدار الذاتي -- العراق